2011
DOI: 10.1590/s1984-46702011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Artificial nests as an alternative to studies of arboreal small mammal populations: a five-year study in the Atlantic Forest, Brazil

Abstract: ABSTRACT. Despite the great diversity of Brazilian Atlantic forest small mammals, natural history of most species is unknown due to their cryptic and nocturnal habits, but also due to the inadequacy of methods to capture some species, especially those of arboreal habits. A new technique, based on the use of artificial nests (AN) to record arboreal marsupials, is presented. Artificial nests were combined with traditional live traps to study the population ecology of four didelphid marsupial species. After 62 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
9
0
3
Order By: Relevance
“…One may suggest trap-happy individuals or great shifts in population parameters could be the cause. This is unlikely because the experiment duration was short and overall population oscillation showed the same decreasing pattern shown every year during the spring and summer in the study area (see Loretto & Vieira 2011, Ferreira et al 2016, and other sites (e.g. O'Connell 1989, Andreazzi et al 2011).…”
Section: Field Experiments -Bait Testmentioning
confidence: 88%
“…One may suggest trap-happy individuals or great shifts in population parameters could be the cause. This is unlikely because the experiment duration was short and overall population oscillation showed the same decreasing pattern shown every year during the spring and summer in the study area (see Loretto & Vieira 2011, Ferreira et al 2016, and other sites (e.g. O'Connell 1989, Andreazzi et al 2011).…”
Section: Field Experiments -Bait Testmentioning
confidence: 88%
“…Although the study area is close to the type locality of M. paulensis ("Therezopolis", Tate 1931; Voss et al 2004), we have never confirmed the presence of this species in the sampling grids, which could lead to a more intense habitat segregation and diet specialization. Interspecific competition was recorded for Gracilinanus agilis and G. microtarsus in gallery forests in a Cerrado-Atlantic Forest transition area (Azevedo et al 2022) and the vertical stratification in the use of space by both species was shown using the spool and line (Cunha & Vieira 2002, Loretto & Vieira 2008) and artificial nests (Loretto & Vieira 2011) methods. In both studies, M. incanus used mostly the ground, while G. microtarsus only the arboreal stratum.…”
Section: Discussionmentioning
confidence: 99%
“…Tubelis (2000) found lactating female G. microtarsus using bamboo nest boxes on several occasions, and this species also uses tree hollows (Caceres and Pichorim, 2003). More recently, Loretto and Vieira (2011), through the systematic use of a large number of artificial nests, have recorded five species of Didelphidae in such nest-boxes in an Atlantic forest site near Rio de Janeiro (Brazil). Like Hyladelphys, nests built by G. microtarsus are composed mainly of dry leaves and have a central chamber where individuals rest (Caceres and Pichorim 2003).…”
Section: Discussionmentioning
confidence: 99%